(untitled) (BIRDEM Medical Journal, 2012)
Background and objective: Neonates with birth weight <1500 gm constitute approximately 4-7% of all live births. Mortality in this group is very high, contributing to as much as 30% of early neonatal death. This study was done to evaluate the morbidities associated with preterm neonates with birth weight < 1500 gm and possible factors determining the death of these babies. Methods: This study was done at Special Care Baby Unit (SCABU), BIRDEM Hospital from January to October 2010. The medical records of neonates with birth weight <1500 gm admitted in SCABU during the study period were retrospectively reviewed. The outcome measure was in-hospital death. Univariate analysis was done to determine the risk factors of mortality. Results: Total 64 babies with birth weight <1500 gm were admitted during this study period. Mean gestational age was 30.76 (± 2.97) weeks, mean birth weight was 1182 (±283) gm. Jaundice (59.4%), Thrombocytopenia (57.8%), apnoea (53.15), sepsis (45.3%) feeding intolerance (43.8%), and RDS (23.4%) were common co-morbidities in these neonates. Among 64 babies more than one-third died (36%). Risk factors for mortality were gestational age less than 30 wks (OR: 7.73; 95% CI: 2.43-24.53), weight <1000 gm (OR: 4.93; 95% CI: 1.28-18.87), RDS (OR: 13.81; 95% CI: 13.81- 57.86) and baby who required mechanical ventilation (OR: 61.66; 95% CI: 12.54- 303.22). Conclusion: Extreme low birth weight (birth weight <1000 gm), prematurity (gestational age <30 wks) and RDS were the significant risk factors for mortality in this study population. Prevention of prematurity and appropriate management of RDS may reduce the mortality of these neonates. DOI: http://dx.doi.org/10.3329/birdem.v2i1.12356 Birdem Med J 2012; 2(1) 19-22